Effects of Different Pediatric Drugs on the Color Stability of Various Restorative Materials Applicable in Pediatric Dentistry. (10th January 2017) - Tüzüner, Tamer; Turgut, Sedanur; Baygin, Ozgul; Yilmaz, Nagehan; Tuna, Elif Bahar; Ozen, Bugra
Abstract : Background . The chronic recommendation of pediatric drugs could exhibit erosive and cariogenic problems. Objective . To evaluate the effects of different pediatric drugs on the color stability of various restorative materials. Methods . Five specimens (1 mm × 3 mm) were prepared and immersed in ten different pediatric drugs and agitated every 8 hours daily for 2 min up to 1 week. Between immersion periods, the samples were stored in artificial saliva. After 1-week period, Δ E ⁎ values were calculated. Two-way ANOVA and Fisher's LSD test were used for statistical analysis at a level of p < 0.05 . Results . Δ E ⁎ values were only significantly influenced by restorative material factor p < 0.001 and varied in the range of 2.08 and 6.55 units for all drugs/restorative materials. The highest Δ E ⁎ was found in Ferrosanol B-composite ( 6.55 ± 1.38 ) and the lowest one was found in Dolven-glass ionomer ( 2.08 ± 0.40 ) pairwise. The most prominent Δ E ⁎ value elevations were obtained in composite material compared to the compomer and/or glass ionomers in Macrol, Ferrosanol B, and Ventolin (p < 0.001 ; for all) and also for other drugs p < 0.05 . Dolven exhibited significantly higher values compared to Augmentin p = 0.021, Macrol p = 0.018, and Ventolin p = 0.013 in compomer group. Conclusion . The clinically perceptible color changes for tested composite/pediatric drug pairwise can be more problematic than compomer and glass ionomers in pediatric dentistry.